Anti-romance in Arms and the Man - Kandel, Churamoni (Literary Studies, 2025)
This study examines and interprets Arms and the Man through the lens of anti-romanticism and literary realism, focusing on how Shaw dismantles the idealized views of love and war. In contrast to the Victorian Age’s romanticization of these themes, Shaw defies traditional romantic ideals by revealing the truths they obscure. Through characters like Sergius, who embodies conventional heroism, Shaw portrays society’s superficial valorization of war, where soldiers receive the status of noble heroes. Sergius’s grandiose actions embody society’s naïve view of war as an honorable, almost theatrical pursuit. However, Shaw introduces Bluntschli, a Swiss mercenary whose realistic views expose the disillusionment underlying such heroism. Bluntschli, who prioritizes survival over glory, carries chocolates instead of ammunition, embodying a soldier’s natural inclination to preserve life rather than sacrifice it for abstract ideals. Similarly, Shaw critiques romanticized love through the relationship between Raina and Sergius. Initially, Sergius’s heroic ideal captivates Raina, but her encounters with Bluntschli awaken her to a pragmatic view of love. Disillusioned by Sergius’s bravado, she ultimately gravitates toward Bluntschli, symbolizing her rejection of romantic ideals. By elevating Bluntschli, the play’s anti-hero, Shaw redefines the qualities worth admiring in individuals, shifting focus from empty heroism to grounded realism. This study employs a qualitative approach to reveal Shaw’s complex portrayal of human relationships, challenging audiences to reconsider the alluring but deceptive nature of romantic ideals